Low-tech Highly Efficient Radiotechnical Solutions for Meteors and Satellite Observations - Vovk, V.S.; Shulga, O.V.; Sybiryakova, Ye.S.; Kaliuzhniy, M.P.; Bushuev, F.I.; Kulichenko, M.O. (Science and Innovation, 2024)
Single-station technique of meteors’ observation using inexpensive receivers is developed. The receivers are also suitable for observing active artificial Earth’s satellites on solar-synchronous orbits when measuring the Doppler shift frequency at which they emit.